2021
DOI: 10.3389/fnbeh.2021.671017
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Expression of Contextual Fear in Male and Female Rats

Abstract: The study of fear conditioning has led to a better understanding of fear and anxiety-based disorders such as post-traumatic stress disorder (PTSD). Despite the fact many of these disorders are more common in women than in men, the vast majority of work investigating fear conditioning in rodents has been conducted in males. The goal of the work presented here was to better understand how biological sex affects contextual fear conditioning and expression. To this end, rats of both sexes were trained to fear a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
(72 reference statements)
7
9
1
Order By: Relevance
“…Greater freezing for the Remote groups could reflect incubation of fear, or it could reflect weaker conditioning in the Recent groups. Secondly, we did not detect any sex differences in context retrieval, which is consistent with some of the literature regarding context fear [but see, e.g., Maren et al (1994) , Poulos et al (2015) , and Russo and Parsons (2021) ]. For example, Dachtler et al (2011) observed similar freezing between male and female wild-type mice when they returned to the conditioning context after a 24-h retention period.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Greater freezing for the Remote groups could reflect incubation of fear, or it could reflect weaker conditioning in the Recent groups. Secondly, we did not detect any sex differences in context retrieval, which is consistent with some of the literature regarding context fear [but see, e.g., Maren et al (1994) , Poulos et al (2015) , and Russo and Parsons (2021) ]. For example, Dachtler et al (2011) observed similar freezing between male and female wild-type mice when they returned to the conditioning context after a 24-h retention period.…”
Section: Discussionsupporting
confidence: 90%
“…For example, an early study found that male rats froze more than females when re-exposed to the original conditioning context (Maren et al, 1994). While this finding has been replicated (Pryce et al, 1999;Chang et al, 2009;Poulos et al, 2015;Colon et al, 2018;Russo and Parsons, 2021) there are also contradicting reports in the literature (e.g., Dachtler et al, 2011;Fenton et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…We found a main effect for Time [ F (4, 32) = 46.53, P < 0.0001], but not Sex [ F (1, 8) = 0.7709, P = 0.4055] and there was not a Time X Sex interaction [ F (4, 32) = 0.6453, P = 0.6342], indicating that male and female rats performed similar during the training session. Notably, while several labs have reported conflicting results in whether a sex difference exists on this task using the same species and strain as us (Graham et al, 2009 ; Russo and Parsons, 2021 ), we have previously reported that male and female rats show similar fear to the context during the testing session when using identical training parameters (Devulapalli et al, 2021 ). In total, we found 1,261 and 476 K48 polyubiquitinated proteins in females and males, respectively, of which 378 overlapped between sexes ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 71%
“…However, studies on the correlation between uremic toxin and inflammatory reactivity according to chronic kidney disease are still insufficient, and further studies are needed. In addition, the expression of contextual fear memory showed differences according to gender in the previous study results [47]. Therefore, mechanistic differences may occur for hippocampal dysfunction caused by chronic renal failure according to gender, and various memory-related behavioral tests and various effect mechanism studies are needed to investigate the relationship.…”
Section: Discussionmentioning
confidence: 71%